Floods Impacts on the Socio-Economic of Livelihoods in Paktia Afghanistan - Abdul Rashid Wiar; Nazir Khan Mohammadi (International Journal for Research in Applied Sciences and Biotechnology, 2021)
This study investigated the impact of floods on the socio-economic status of livelihoods for the people of Afghanistan's Paktia province and the livelihoods of those who live there. The research team used both quantitative and qualitative approaches in their work. Discussions were held with key stakeholders at the provincial and community levels, as well as with randomly selected households, as part of the study. The information was gathered through the use of quantitative Household Questionnaires and qualitative Key Informant Interviews. People's socioeconomic livelihoods and critical aspects such as agriculture, health, education, housing, water and sanitation, and property were found to have been negatively impacted by floods according to the findings of the study. As a result, any negative impact on livelihood would result in lower household incomes and lower purchasing power for households. In Paktia, as in many other parts of Afghanistan, there has been extensive deforestation. In recent years, devastating floods have resulted as a result of this. The following are the most important recommendations made: Since communities have expressed a desire to relocate permanently to higher ground, the government and key stakeholders should engage them in the process of relocating permanently to higher ground. Their relocation should be accompanied by the provision of all necessary social amenities, such as schools, hospitals, infrastructure, water, and agricultural support, for a period of three (3) years to allow the households to settle in the new location. It should also be taken in the newly established settlement area. A deliberate policy should be implemented to compel communities, particularly in rural areas, to construct houses out of durable materials and away from flood-prone areas, which would be beneficial. Communities should be encouraged to expand the area under cultivation on upland land in order to improve food security and household income. Both non-flooding and flood-prone areas should be clearly delineated by the appropriate authorities. During floods, the non-flooding areas can be used as a makeshift temporary shelter for the settlements. Construction of dams should be considered as a means of capturing the surplus water. This could be used to irrigate the garden. Consideration should be given to the construction of canals into the main Kurrama River.